Continuous low-dose cyclophosphamide and prednisone in the treatment of relapsed/refractory multiple myeloma with severe heart failure. Issue 10 (October 2014) - Zhou, Fan; Ling, Chenhui; Guo, Lieping; Wei, Wei; Li, Lu; Shi, Haotian; Hou, Jian
Abstract Patients with relapsed/refractory (R/R) multiple myeloma (MM) complicated by severe heart failure typically do not tolerate conventional chemotherapy. Our previous study indicated that R/R MM patients with severe comorbidities could benefit from continuous low-dose oral cyclophosphamide and prednisone (CP regimen). We hereby performed a study of 56 R/R MM patients with severe heart failure (New York Heart Association class ≥ III) receiving the treatment of CP regimen. Among the 54 evaluable patients, clinical benefit was noted in 63.0% (complete response, 3.7%; very good partial response, 7.4%; partial response, 48.1%; stable disease, 3.7%). The median overall survival (OS) and progression-free survival (PFS) were 8 and 6 months. The left ventricular ejection fraction (LVEF) and the serum levels of B-type natriuretic peptide (BNP) were improved significantly. Slight adverse events were observed. In summary, the CP regimen is effective in R/R MM patients complicated with severe heart failure.